Effect of compensation, work environment and communication on employee performance in ud. djaya listrik and material - Esthi, Raniasari Bimanti (FORUM EKONOMI, 2021)
Demand for building materials and electrical appliance products in Bekasi, West Java continues to increase due to the growth of the property sector and various consumers preferences. This has contributed to the growth of this supports business. The objective of this study is to determine the effect of compensation, work environment and communication on employee performance with a case study at UD. Djaya Electricity and Materials (UD. DEM). The sampling method was purposive sampling technique because UD. DEM selected as a company that sells and distribute building materials and electrical appliance products for wholesale and retail, already has 10 branches in Bekasi and 50 employees. Data collection was conducted through observation, distributing questionnaires and literature study. The analysis method used in this research is validity, reliability, classical assumption, multiple linear analysis and hypothesis test. The results showed that compensation and work environment partially had a positive effect on employee performance, while communication partially had no effect on employee performance.